Music, lyrics, and the Bengali book: Hindustani musicology in Calcutta, 1818-1905 - Williams, R (Oxford University Press, 2016)
From theoretical treatises to songbooks, literature relating to Hindustani music proliferated in nineteenth-century Bengal. With few exceptions, these innovative Bengali works have received scant attention in studies of colonial-era music, which have focused instead on Anglophone scholarship. Bringing a wider range of vernacular texts into the analysis nuances the landscape of intellectual production, and indicates that nationalist or reformist interests pertained to but one public arena, jostling against several others. This article examines treatises dealing with the theory and history of Hindustani music, demonstrating the journey of Bengali musicology from Persian antecedents to its own system. The field of print production is then diversified further through an analysis of song collections, a major genre that disrupts any notion of a uniform sphere of transmission, reading, and listening. Rather than thinking of nineteenth-century music purely in terms of the colonial relationship, this article foregrounds a wider set of competing cultural and aesthetic considerations.